Grazing by reindeer in subarctic coniferous forests – how it is affecting three main greenhouse gas emissions from soils - Köster, Kajar; Köster, Egle; Berninger, Frank Alexander; Pumpanen, Jukka Sakari (European Geophysical Society, 2018)
Non peer reviewed